2013
DOI: 10.1002/dev.21191
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related face processing bias in infancy: Evidence of perceptual narrowing for adult faces

Abstract: Recent data demonstrate a perceptual processing advantage for adult faces in both adults and young children, suggesting that face representation is shaped by visual experience accumulated with different face-age groups. As for species and race, this age bias may emerge during the first year of life as part of the general process of perceptual narrowing, given the extensive amount of social and perceptual experience accumulated with caregivers and/or other adult individuals. Using infant-controlled habituation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 57 publications
16
62
0
Order By: Relevance
“…Given that young infants typically prefer familiar stimuli in the social domain, it was hypothesised that Caucasian 3.5- and 6-month-old infants would attend more to Caucasian adult than Caucasian infant stimuli, since adults represent the most highly familiarised age group in the environment of infants. We also predicted that 3.5- and 6-month-old Caucasian infants would not show an age preference for other-race (Asian) faces, in line with the finding that infant gender preference is restricted to own-race faces (Liu et al, 2015a; Quinn et al, 2008) and the adult face bias is confined to own-race faces in 3-year-olds (Macchi Cassia et al, 2014b). To weaken potential low-level explanations for any preferences detected, stimuli were presented in an inverted orientation in a separate condition.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Given that young infants typically prefer familiar stimuli in the social domain, it was hypothesised that Caucasian 3.5- and 6-month-old infants would attend more to Caucasian adult than Caucasian infant stimuli, since adults represent the most highly familiarised age group in the environment of infants. We also predicted that 3.5- and 6-month-old Caucasian infants would not show an age preference for other-race (Asian) faces, in line with the finding that infant gender preference is restricted to own-race faces (Liu et al, 2015a; Quinn et al, 2008) and the adult face bias is confined to own-race faces in 3-year-olds (Macchi Cassia et al, 2014b). To weaken potential low-level explanations for any preferences detected, stimuli were presented in an inverted orientation in a separate condition.…”
supporting
confidence: 78%
“…Instead, research indicates that adults and children are better at recognizing adult faces than children’s faces unless they have specific experience with the latter category. A recent study indicates that 9-month-olds recognize adult faces better than infant faces, whereas 3-month-olds recognize faces from both age classes equally well (Macchi Cassia, Bulf, Quadrelli, & Proietti, 2014a). Thus, it appears that early in development, perceptual processes become tuned to adult faces because these are the faces which infants experience most frequently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The former refers to formation of discrete groups composed of similar but discriminable individuals, whereas the latter refers to formation of discrete groups of exemplars that are difficult to discriminate. Regarding discrimination, Macchi Cassia et al (2014) reported that 9-month-olds display a downturn in discrimination of infant faces compared to adult faces. These results imply that infants in the current study engaged in categorization of adult faces and categorical perception of infant faces.…”
Section: Discussionmentioning
confidence: 99%
“…This differential exposure results in poor discrimination abilities for infant faces compared to adult faces in 9-month-olds (Macchi Cassia, Bulf, Quadrelli, & Proietti, 2014). Infants might thus have a more structured representation of adult faces compared to other-age faces due to experience.…”
mentioning
confidence: 99%